PERANCANGAN APLIKASI CLICKOST BERBABIS WEB MENGGUNAKAN METODE HMVC (HIERARCHICAL MODEL VIEW CONTROLLER) SEBAGAI SISTEM PENCARIAN DAN PROMOSI INDEKOS DI KOTA PADANG - Randi Proska Sandra; Ahmaddul Hadi; Yasdinul Huda (Universitas Negeri Padang, 2017)
Rent-house’s Searching and Promotion in Padang city using brochure or leaflet which sticked in public place. It could be ‘wild-advertising’ in the public spaces. The other problems of Rent-house in Padang city is lack on resident’s security and irrelevant information between promotion material and reality. Clickost web-based application is the means to force the Rent-house business in Padang city move to digital technology to expand the market and ease the potential resident. Clickost web-based application using HMVC (Hierarchical Model View Controller) architecture with OOP (object oriented programming) approach and UML’s model. Clickost using several language programming including PHP, CSS, HTML5, and Javascript, CodeIgniter as framework and MySQL as database. This Application will spend the time, cost and energy efficiently in handling Rent-house’s searching and promotion. Keywords : Clickost, Website, Rent-house, HMVC, Searching and promotion